PSYCHOMETRIC PROPERTIES OF THE GEORGIAN VERSIONS OF THE BIG FIVE QUESTIONNAIRES - Martskvishvili , Khatuna; Sordia , Natia; Neubauer , Aljoscha (Georgian Psychological Journal, 2022)
The goal of the ﬆudy is to examine the psychometric properties of the Georgian versions of the Big Five Inventory (BFI; John & Strivaﬆava, 1999) and the Ten Item Personality Inventory (TIPI; Gosling, Rentfrow, & Swann, 2003), the two inﬆruments measuring the Big Five model. 866 individuals partic- ipated in the ﬆudy examining the Georgian version of BFI and 377 individuals in the development of the Georgian version of TIPI. According to the results, the factor ﬆructure of both inﬆruments replicates the ﬁve-factor model observed in other cultures. The reliability coeﬃcients correspond to the minimum levels recommended for personality queﬆionnaires/inventories. However, these levels turned out to be lower for TIPI. The inﬆrument validity is proved by their logical correlations with the theoretically relevant conﬆructs, namely with the Six-Factor model, aversive personality traits, and emotional intelli- gence. We can conclude that due to the factor ﬆructure, expected relationships with other conﬆructs and ﬆatiﬆical signiﬁcance, the Georgian versions of both inﬆruments measuring the Big Five can be used for future research.